Optical forces in silicon nanophotonics and optomechanical systems : science and applications - Chin, Lip Ket (2021)
Light-matter interactions have been explored for more than 40 years to achieve physical modulation of nanostructures or the manipulation of nanoparticle/biomolecule. Silicon photonics is a mature technology with standard fabrication techniques to fabricate micro- and nano-sized structures with a wide range of material properties (silicon oxides, silicon nitrides, p- and n-doping, etc.), high dielectric properties, high integration compatibility, and high biocompatibilities. Owing to these superior characteristics, silicon photonics is a promising approach to demonstrate optical force-based integrated devices and systems for practical applications. In this paper, we provide an overview of optical force in silicon nanophotonic and optomechanical systems and their latest technological development. First, we discuss various types of optical forces in light-matter interactions from particles or nanostructures. We then present particle manipulation in silicon nanophotonics and highlight its applications in biological and biomedical fields. Next, we discuss nanostructure mechanical modulation in silicon optomechanical devices, presenting their applications in photonic network, quantum physics, phonon manipulation, physical sensors, etc. Finally, we discuss the future perspective of optical force-based integrated silicon photonics.